Analisis Pengaruh Remitasi, Investasi Asing Langsung, Import dan Pertumbuhan Ekonomi di Indonesia - Regina Septriani; Ariusni Ariusni (Universitas Negeri Padang, 2021)
This study examined and analysis the effect of remittances, foreign direct investment, imports, and economic growth in Indonesia in the long run and short run. This study using Error Correction Model (ECM) method and using the annual time series data from 1989 to 2018. This study found that: (1) remittance have an insignificant positive effect on economic growth in the long run and short run,(2)foreign direct investment have a significant positive impact on economic growth in the long run and short run, (3) import have an insignificant positive impact on economic growth both in the long run and short run. To increase the economic growth in the future, this study suggests the government to decresing imports of consume goods and increasing the inflow of capital goods, raw material goods, remittances and foreign direct investment.